Comparative Legal Perspectives on Bullying in Educational Environments: Regulatory Gaps and Reform Imperatives in Indonesia, Malaysia, and Vietnam - Astuti, Pudji; Bin Awang, Mohd Badrol; Mahardhika, Vita; Rusdiana, Emmilia (Jambura Law Review, 2025)
Bullying in educational settings is a criminal offense that can hinder the learning process and negatively impact both victims and perpetrators mentally, socially, physically, and academically. The legal gap in this study is linked to the inaccurate enforcement of laws related to bullying in educational settings, emphasizing punishment rather than optimal recovery measures for victims. This study aims to analyze and provide a legal critique of the regulation of bullying in Indonesia, comparing it with that of Malaysia and Vietnam. This normative-comparative legal study prioritizes a comparative legal approach as the primary approach, supplemented by conceptual and statutory approaches. This study finds that criminal law plays a significant role in preventing and addressing bullying by imposing sanctions on perpetrators and providing protection for victims. The comparison of laws regulating bullying in Indonesia, Malaysia, and Vietnam confirms that the lack of community involvement and participation, particularly parents and teachers or educators, in the restorative justice process for children as perpetrators and victims of bullying in educational settings has not received optimal attention. The involvement of parents and teachers is crucial to ensure an effective restorative justice process, guaranteeing the fulfillment of children's rights and their best interests. This study recommends that updating the criminal law governing bullying in educational settings is crucial to ensure the rights of children, both as perpetrators and victims. This update requires a shift in the orientation of criminal law, which is currently only regulated in regulations outside the National Education System Law, by adding specific provisions for bullying within the National Education System Law.